Cocreating Value in Teaching and Learning Centers. (14th March 2013) - Schumann, David W.; Peters, John; Olsen, Taimi
Abstract: In addition to addressing the history of and rationale for the teaching and learning center (TLC) as a means of achieving lasting professional development of the faculty, Schumann, Peters, and Olsen introduce the concept of cocreating value that not only facilitates the success of the TLC but also has the potential to permeate the educational fiber of the entire college or university.